THE EFFECT OF EDUCATION LEVEL, ACCOUNTING TRAINING, AGE OF BUSINESS AND BUSINESS SCALE OF UMKM ACTORS ON THE USE OF ACCOUNTING INFORMATION IN BOYOLALI DISTRICT - Dwiyana Cahyani Sara Pertiwi; Rukmini Rukmini; Suprihati Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Indonesia was a country whose economy is mostly supported by the UMKM sector, including in the Boyolali region. This study aims to determine the effect of education level, accounting training, business age and business scale of MSME actors on the use of accounting information on UMKM in Ngemplak Boyolali District. This type of research is descriptive quantitative research. The data collection technique used an instrument in the form of a closed questionnaire with a Likert scale. The sample in this study is the perpetrators of UMKM in the culinary field in the District Ngemplak Boyolali as many as 50 people taken by simple random sampling. The data analysis method used multiple linear regression analysis with the help of SPSS program. The results showed that the level of education, accounting training, business age and business scale of UMKM actors affected the use of accounting information in Ngemplak Boyolali District either simultaneously or partially. The results of the analysis of the coefficient of determination obtained a value of 88.8%. This can be interpreted that the level of education, accounting training, business age and business scale of UMKM actors are able to explain the variation of changes in the variable use of accounting information and the remaining 11.2% is explained by other variables outside the research model.